Innovations in WASH Impact Measures : Water and Sanitation Measurement Technologies and Practices to Inform the Sustainable Development Goals - Thomas, Evan; Andrés, Luis Alberto; Borja-Vega, Christian; Sturzenegger, Germán (Washington, DC: World Bank, 2017)
The new 2030 Agenda for Sustainable Development includes water, sanitation, and hygiene (WASH) at its core. A dedicated Sustainable Development Goal (SDG 6) declares a commitment to “ensure availability and sustainable management of water and sanitation for all.” Monitoring progress toward this goal will be challenging: direct measures of water and sanitation service quality and use are either expensive or elusive. However, reliance on household surveys poses limitations and likely overstated progress during the Millennium Development Goal period.